Factors influence women entrepreneur business success - Norain, Doi (2015)
Nowadays, the number of women entrepreneurs involve in the business is kept increasing year by year. Hence this paper sets out to survey the seven factors that influence the women entrepreneur business success. The independent variables are socio-economic and culture; market and network; family support; government support; financial and fund support; social media and self- motivation. A questionnaire was used for data collection, and it was distributed to the women entrepreneurs in the northern region of Malaysia as the sample of this study. Multiple regression analysis was used to analyze the research hypotheses. The results showed that socio-economic and culture; market and network; family support; and self- motivation have significant and positive influence on women entrepreneur business success. The findings also revealed negative and significant link on socio-economic and culture factor with women business success, because result shows refuted hypothesis which led to the new finding of this study. Meanwhile, government support; financial and fund support; and social media did not have significant influence to the women entrepreneur business success. Research recommended for further study in the future, in order to investigate other important factors could influence the women entrepreneur business success and also a deeper investigation on the factors that not significant. It is also hoped that this study could contribute to the entrepreneurial literatures as well as practices